Middlemen, non-profits, and poverty - Nancy H. Chau; Hideaki Goto; Ravi Kanbur (Institute for the Study of Labor (IZA), 2009)
In many markets in developing countries, especially in remote areas, middlemen are thought to earn excessive profits. Non-profits come in to counter what is seen as middlemen's market power, and rich country consumers pay a fair-trade premium for products marketed by such non-profits. This paper provides answers to the following five questions. How exactly do middlemen and non-profits divide up the market? How do the price mark up and price pass-through differ between middleman and non-profits? What is the impact of non-profits entry on the wellbeing of the poor? Should the government subsidize the entry of non-profits, or the entry of middlemen? Should wealthy consumers in the North pay a premium for fair trade products, or should they support fair trade non-profits directly?
Keywords: F15; I32; L3; 330; Middlemen; non-profits; poverty; market access; Exporthandel; Handelsspanne; Gewinn; Fairer Handel; Nonprofit-Organisation; Markteintritt; Armut; Armutspolitik; Nord-Süd-Beziehungen; Entwicklungsländer